Pedometer-based walking intervention with and without group support among sedentary adults in primary care patients in north-east Malaysia: a randomized controlled trial (Bangladesh Journal of Medical Science, 2018)
Background: Many studies have shown that pedometer is an effective motivational tool to promote walking however there is lack of evidence which combines pedometer and group support in motivating patient to increase their physical activityObjective: To determine the effectiveness of pedometer and group support versus pedometer only on physical activity level and cardiovascular risk factors among sedentary adults in north-east MalayMethods: This was a prospective randomized comparative trial. Eighty participants were randomly assigned to pedometer-based walking program plus group support ( N=40) or pedometer-based walking program only (N=40) for 12 weeks. Both groups received physical activity counselling. The intervention group had monthly group meeting for support, motivation and also walking activities. Measurements for step-counts, 7-day physical activity recall, body mass, BMI, waist and hip circumference, blood pressure, total cholesterol, HDL cholesterol and fasting blood sugar were taken at baseline and at week 12. Analyses were performed using repeated measures ANOVA and analysis of co-variance (ANCOVA).Results and Discussion: Sixty two participants completed the study. The mean age in the intervention group were 48 (4.43) years old and 47 (5.08) years old in the control group. There were significant improvements in the intervention group in terms of step-counts (p < 0.001), weight (P0.05) compared to control group. However there was no significant difference in term of other health outcome.Conclusion A pedometer-based walking program, incorporating a physical activity consultation and group support, is effective in promoting walking and improving health outcome in community based individuals. Studies of longer duration need to be done to see the sustainability of the above intervention.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.52-57